2020
DOI: 10.2147/ijn.s242919
|View full text |Cite
|
Sign up to set email alerts
|

<p>Improved Immunoregulation of Ultra-Low-Dose Silver Nanoparticle-Loaded TiO<sub>2</sub> Nanotubes via M2 Macrophage Polarization by Regulating GLUT1 and Autophagy</p>

Abstract: Introduction: The bone regeneration of endosseous implanted biomaterials is often impaired by the host immune response, especially macrophage-related inflammation which plays an important role in the bone healing process. Thus, it is a promising strategy to design an osteo-immunomodulatory biomaterial to take advantage of the macrophage-related immune response and improve the osseointegration performance of the implant. Methods: In this study, we developed an antibacterial silver nanoparticle-loaded TiO 2 nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 71 publications
1
36
0
1
Order By: Relevance
“…Additionally, surface immobilization using Ag nanoparticles has been frequently used in various antibacterial implants, such as wound dressings and catheters ( Besinis et al, 2017 ; Choi et al, 2019 ). Recently, the immunoregulatory role of Ag nanoparticle-modified surface on immune cells has also been reported ( Chen et al, 2020 ). PCL, a high-performance bioresorbable and biocompatible polymer, has been approved by the US Food and Drug Administration (FDA) for soft and hard tissue repair ( Mondal et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, surface immobilization using Ag nanoparticles has been frequently used in various antibacterial implants, such as wound dressings and catheters ( Besinis et al, 2017 ; Choi et al, 2019 ). Recently, the immunoregulatory role of Ag nanoparticle-modified surface on immune cells has also been reported ( Chen et al, 2020 ). PCL, a high-performance bioresorbable and biocompatible polymer, has been approved by the US Food and Drug Administration (FDA) for soft and hard tissue repair ( Mondal et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between TNTs and macrophage polarization has been described in many studies, both in modified TNTs. Previous studies have reported that nano‐arrays on the surface of titanium plates can regulate macrophage polarization towards M2‐type by activating autophagy 14 . Wang et al 15 have also found that TNTs of different diameters could regulate the polarization of macrophages.…”
Section: Resultsmentioning
confidence: 98%
“…Previous studies have reported that nano‐arrays on the surface of titanium plates can regulate macrophage polarization towards M2‐type by activating autophagy. 14 Wang et al 15 have also found that TNTs of different diameters could regulate the polarization of macrophages. The results revealed that the TNTs regulated macrophage polarization by influencing cell metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…Administration of this NP into CIA mice achieved a reduction of TNF-α, IL-6, and IL-1β within the synovium [123]. On the topic of re-polarization, silver NPs have been shown to increase intracellular Ag + , promoting macrophage polarization towards an M2 phenotype through inhibition of phosphoinositide 3-kinase (PI3K)/ Akt signaling, decreasing expression of glucose transporter expression, and inducing autophagy [124]. In a similar macrophage re-educating strategy, Yang et al [125] functionalized a silver NP with folate and successfully induced the death of inflammatory macrophages, or their polarization towards an M2 phenotype in the CIA murine model [125].…”
Section: Macrophagesmentioning
confidence: 99%